2016
DOI: 10.7567/jjap.55.08pc06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of valence band top and electron affinity of SiO2 and Si-based semiconductors using X-ray photoelectron spectroscopy

Abstract: An evaluation method for the energy level of the valence band (VB) top from the vacuum level (VL) for metals, dielectrics, and semiconductors from the results of X-ray photoelectron spectroscopy (XPS) is presented for the accurate determination of the energy band diagram for materials of interest. In this method, the VB top can be determined by the energy difference between the onset of VB signals and the cut-off energy for secondary photoelectrons by considering the X-ray excitation energy (hν). The energy le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 23 publications
(33 reference statements)
1
38
0
3
Order By: Relevance
“…The illustration contains the range of the redox levels of the Ag + /Ag half-cells E (Ag + /Ag) shown in Figure 2 a; the work functions of silver Φ Ag = 4.37 eV ± 0.37 eV [ 65 , 66 , 67 , 68 , 69 ] and hydrogen-terminated silicon Φ Si–H = 4.36 eV ± 0.19 eV in vacuum [ 70 ]; the Fermi energy E F ; and the energetic levels of valence and conduction bands of hydrogen-terminated silicon ( E v (Si–H) = −0.68 eV and E c (Si–H) = 0.65 eV) [ 71 ]. The positions of the valence and conduction bands of bulk silicon ( E v (Si bulk ) = −0.41 eV and E c (Si bulk ) = 0.71 eV) were calculated based on the difference of the work function of silicon Φ Si = 4.76 eV ± 0.34 eV [ 72 ], the electron affinity of silicon χ = 4.05 ± 0.03 eV [ 73 ] and the band gap of 1.12 eV [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The illustration contains the range of the redox levels of the Ag + /Ag half-cells E (Ag + /Ag) shown in Figure 2 a; the work functions of silver Φ Ag = 4.37 eV ± 0.37 eV [ 65 , 66 , 67 , 68 , 69 ] and hydrogen-terminated silicon Φ Si–H = 4.36 eV ± 0.19 eV in vacuum [ 70 ]; the Fermi energy E F ; and the energetic levels of valence and conduction bands of hydrogen-terminated silicon ( E v (Si–H) = −0.68 eV and E c (Si–H) = 0.65 eV) [ 71 ]. The positions of the valence and conduction bands of bulk silicon ( E v (Si bulk ) = −0.41 eV and E c (Si bulk ) = 0.71 eV) were calculated based on the difference of the work function of silicon Φ Si = 4.76 eV ± 0.34 eV [ 72 ], the electron affinity of silicon χ = 4.05 ± 0.03 eV [ 73 ] and the band gap of 1.12 eV [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, a good possibility exists that unknown phase have indirect and direct E g values of 2.75 and 2.85 eV, respectively. A contribution to the absorption from the matrix is impossible as for SiO 2 E g ≅ 9 eV 26 . Raman characterization was carried out on both samples, grown on Si and quartz substrates.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, the Al Kα emission line with an energy of 1486.6 eV was used, and silicon was chosen to be the reference material because its core lines are well defined. First, the calibration allows one to shift the kinetic energy scale by choosing the WF d value to make the position of spectral lines appropriate to the KE values counted from the vacuum level of the silicon substrate . Second, it allows one to obtain the precision of kinetic energy determination to ≈±0.05 eV over the whole energy scale due to the narrowness of the XPS core lines .…”
Section: Resultsmentioning
confidence: 99%
“…First, the calibration allows one to shift the kinetic energy scale by choosing the WF d value to make the position of spectral lines appropriate to the KE values counted from the vacuum level of the silicon substrate. [44] Second, it allows one to obtain the precision of kinetic energy determination to %AE0.05 eV over the whole energy scale due to the narrowness of the XPS core lines. [45] XPS spectra of the sample under study after Th implantation are shown in Figure 6.…”
Section: Uv Photons Energy Measurementmentioning
confidence: 99%